Ambiguity of Television’s Religious Broadcasting Programs: Between Education or Reality - Bono Setyo; Lelita Azaria; Khoiro Ummatin (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
A peaceful life is one of the essential hopes of every individual. This hope was captured as an opportunity by the media industry to produce religious broadcast television programs. Religious programs get viewers’ attention shown through high ratings that can attract advertisers. The problem that occurs is related to broadcast quality. The function of the media is as a means of education and information. This study uses a qualitative approach with a descriptive study to describe the results of the study. The results showed an imbalance of religious broadcast content, which tended to Islamic content. Some programs even display horror and mystical which is not in accordance with the religious content. Almost all religious program broadcasters are stuck on the strength of the program name and the figure of the messenger. This imbalance shows the ambiguity of the function of mass media as an educational medium.